Tindakan Pencegahan Perilaku Bullying Di Lingkungan Raudhatul Athfa Kemlagi Mojokerto - Lus Firdaus Zakiya; Dwi Rahmanto; Aisyah Vitara Aly; Ramanja Situmorang; Awin Septian Danuarta; Rihadatul Ufairoh Habibah Afaf; Ines Maria Sandy; Dyah Ayu Tiara Biru Safira; Afat Ardiansyah; Linda Rahmawati; Aprilia Eka Yunita; Aulia Wulandhari; Ali Wafah; Aziza Rega Istighfarini; Muhammad Ulil Abshor; Kartika Rose Santy; Risma Septiana Linda Sari; Arbiasnyah Rendra Jati Rukmana; Ahmad Syifaul Qulub; Alychia Wydianingrum; Annisa Kudusyana; Ari Cahya; Mochammad Junaedi; Achmad Sulabin (jurnal ABDIMAS Indonesia, 2023)
Bullying is an act of violence committed by an individual or group to another person so that they suffer injuries that have a very serious impact both physically and psychologically. This activity was carried out on December 14, 2023 at schools in Kemlagi Village. This activity was carried out because of the many victims in the current era which are mostly carried out by students, therefore we hold educational counseling on the impact of bullying. This activity was carried out with the aim of fostering and preventing aggressive mindsets and attitudes. This activity was attended by 30 students.